PERILAKU KONSUMTIF IBU RUMAH TANGGA DAN IMPLIKASINYA TERHADAP PENGELOLAAN KEUANGAN KELUARGA DI KABUPATEN GOWA - Nurwahyuni; Jam'an, Andi; Muchran, Muchriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of housewives' consumptive behavior and its implications on family financial management in Gowa Regency. This study uses a quantitative method, with a sample of 93 housewives in Katangka Village, Somba Opu District, Gowa Regency. The data used are primary data obtained through distributing questionnaires using Google Form. The data analysis technique used is simple linear regression processed using SPSS 25 statistical calculations. Based on the results of the t test and simple linear regression test, it shows that housewives' consumptive behavior has a negative and significant effect on family financial management. This is evidenced by a significance value of 0.031 < 0.05. And the regression coefficient result is -0.123 Based on the results of SPSS 25 output, the results of the study partially found that housewives' consumptive behavior has a negative effect on family financial management, especially in Katangka Village, Somba Opu District, Gowa Regency.